2018
DOI: 10.1021/jacs.8b12796
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Allylic Alcohol with Chiral BINOL-Based Alkoxides: A Combination of Experimental and Theoretical Studies

Abstract: The development and characterization of enantioselective catalytic kinetic resolution of allylic alcohols through asymmetric isomerization with chiral BINOL derivatives-based alkoxides as bifunctional Brønsted base catalysts were described in the study. A number of chiral BINOL derivatives-based alkoxides were synthesized, and their structure−enantioselectivity correlation study in asymmetric isomerization identified a promising chiral Brønsted base catalyst, which afforded various chiral secondary allylic alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 97 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…These species have their own intrinsic activities and selectivities as catalysts. The influence of hydrogen bonding in catalysis has been extensively documented, and the hydrogen-bonding ability of the BCF·H 2 O adduct has been previously studied, , and H-bound complexes have been implicated in other examples of BCF catalysis . Related Lewis acid·H 2 O catalysis has been described for other molecular systems , and is likely involved in solid-supported Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…These species have their own intrinsic activities and selectivities as catalysts. The influence of hydrogen bonding in catalysis has been extensively documented, and the hydrogen-bonding ability of the BCF·H 2 O adduct has been previously studied, , and H-bound complexes have been implicated in other examples of BCF catalysis . Related Lewis acid·H 2 O catalysis has been described for other molecular systems , and is likely involved in solid-supported Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral alcohols can be synthesized via (1) multistep transformations from a chiral pool such as terpenes, amino acids, and carbohydrates (Fan et al., 2019, Hung et al., 2019, Brill et al., 2017) or (2) kinetic resolution of racemic alcohols or their derivatives (Liu et al., 2019, Selier et al., 2019, Zhang and Ma, 2018). In addition, asymmetric synthesis such as reduction or nucleophilic addition of prochiral carbonyls recently has been developed (Neves-Garcia et al., 2018, Tsai et al., 2018; Bieszczad and Gilheany, 2017, Nakamura et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, the Yan group established a highly enantioselective kinetic resolution of secondary allylic alcohols 21 , through asymmetric isomerization catalyzed by a newly devised chiral bifunctional BINOL derivatives‐based alkoxide 22 (Scheme 9). [22] A series of γ‐hydroxy substituted enones 21 bearing different substituents proved to be suitable substrates under the action of 5 mol % of catalyst 22 , and delivered the corresponding ( S )‐ 21 in 41–50 % yields with 90–99 % ee, together with the formation of 1,4‐diketones 23 . By mechanistic studies, the authors proposed that the alkoxide moiety in the catalyst 22 was identified as active species, whilst the phenol groups of BINOL had a great influence on the high reactivity and enantioselectivity via H‐bonding interaction.…”
Section: Catalytic Enantioselective Isomerization Of Secondary (Homo)...mentioning
confidence: 99%